Pathogenic Bacteria in Infections of the Respiratory Tract. Autonomous University Hospital Service Antonio Patricio de Alcalá. Cumaná, Sucre State - Militza Guzmán L; Luzmila Albarado I; José Betancourt; Belkis Medina (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2005)
In orden to determine the frequency of bacterial pathogens in the respiratory tract of children between the ages of 0 - 11 years old who attend the emergency service in the Pediatrics ward at the Autonomous Hospital Antonio Patricio de Alcalá in Cumaná, Sucre state during the period from June to November 2001, 150 samples from children with infections in the respiratory tract were analyzed. The microbiological diagnosis was performed using classical methods to identify the microorganisms in clinical samples. The resistance to antibiotics was determined by the agar dilution technique according to the guidelines of the National Committee for Clinical Laboratory Standards (NCCLS). The upper respiratory tract infections (75.00%) exceeded the lower respiratory tract infections. The main cause for medical consultation was pharyngitis (43.00%), followed by otitis (32.00%) and pneumonia (25.00%), and. 62.00% the samples were positive. The microorganisms most frequenct in the upper respiratory tract were Streptococcus bbb-hemolytic group A (24.49%) and Staphylococcus aureus (16.32%) and in the lower respiratory tract Klebsiella pneumoniae (10.20%). The greater percentaje of resistance in the microorganism isolates was for the β-lactamics group.